STRATEGI KESANTUNAN BERBAHASA PADA MASYARAKAT BANJAR - Rissari Yayuk (MABASAN, 2016)
This study titled politeness strategies in Banjar community. The problem raised is how a form of politeness strategies in Banjar community. The purpose was to determine the form of politeness strategies in Banjar community. Methods of research on the subject of politeness strategies in Banjar community is using descriptive method. Collecting data in Bamban village of months of February and March 2016. The results of the research is a form of politeness strategies in Banjar community includes attention to what is needed or preferred opponent said, using solidarity or group identity through a greeting or jargon , offer or promise anything , to avoid overlapping, and clowning.